Studies on the Indian species of Aleuroplatus (Hemiptera: Aleyrodidae), with designation of a neotype puparium for Aleurodes alcocki Peal - Dubey, Anil Kumar; David, B. Vasantharaj (Zootaxa, 2012)
A neotype is designated for Aleurodes alcocki Peal, which is currently in the genus Aleuroplatus, and this species is dis-tinguished from Aleuroplatus pectiniferus Quaintance & Baker. Aleuroplatus cinnamomi Jesudasan & David is recalled from synonymy with A. pectiniferus as a valid species. A key to puparia of the Indian Aleuroplatus species is given.